FRAUD PENTAGON THEORY: INDICATION TOWARD FRAUDULENT FINANCIAL REPORTING ON NON-BANKING SECTOR - Fera Tjahjani; Briantama Maulidza Rizky; Widanarni Pudjiastuti; Nawang Kalbuana (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aimed to analyze the influence of the five elements in fraud pentagon theory to detect an indication of fraudulent financial reporting. Fraud pentagon consists of pressure which is proxied by financial stability, financial target, and external pressure, opportunity which is proxied by ineffective monitoring and nature of the industry, rationalization which is proxied by change of auditor and total accrual ratio, a competence which proxied by change of director, and arrogance which proxied by CEO’s picture frequency. The indication of fraudulent financial reporting which is proxied by restatement serves as the dependent variable. This study uses purposive sampling to select a representative sample. The sample is 37 financial non-banking companies that were listed on Indonesia Stock Exchange during the period 2017-2019, resulting in 111 firm-observation. The collected data is analyzed using logistic regression. The results of this study show that all variables which consist of financial stability, financial target, external pressure, ineffective monitoring, nature of the industry, change of auditor, total accrual ratio, change of director, and CEO’s picture frequency do not have significant influent to the indication of fraudulent financial reporting.